2012
DOI: 10.1111/j.1526-4637.2012.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Pain Analgesia in Chronic Pelvic Pain Patients Using Respiratory-Gated Auricular Vagal Afferent Nerve Stimulation

Abstract: Objective Previous Vagus Nerve Stimulation (VNS) studies have demonstrated anti-nociceptive effects, and recent non-invasive approaches; termed transcutaneous-VNS, or t-VNS, have utilized stimulation of the auricular branch of the vagus nerve in the ear. The dorsal medullary vagal system operates in tune with respiration, and we propose that supplying vagal afferent stimulation gated to the exhalation phase of respiration can optimize t-VNS. Design counterbalanced, crossover study. Patients patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
2
22

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 84 publications
(96 reference statements)
2
171
2
22
Order By: Relevance
“…While the present study was conducted on a healthy population and focused on elucidating the central projections of the ABVN there are reports of cognitive and behavioral effects of t-VNS and VNS, i.e., antinociception [7,29,43,58], anti-depression [22,41,53], and anti-convulsion [10,55,57]. The mechanisms underlying these effects are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the present study was conducted on a healthy population and focused on elucidating the central projections of the ABVN there are reports of cognitive and behavioral effects of t-VNS and VNS, i.e., antinociception [7,29,43,58], anti-depression [22,41,53], and anti-convulsion [10,55,57]. The mechanisms underlying these effects are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above neuroanatomical and brain imaging studies, there is evidence that t-VNS produces cognitive and behavioral effects that are also produced by VNS [7,10,22,29,41,43,53,55,57,58]. Based on conventional neuroanatomy, VNS would be expected to activate the vagal projections beginning centrally at the NTS; therefore, it is likely that t-VNS, via the ABVN, would also activate the NTS.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas electroconvulsive therapy and vagal nerve stimulation are FDA-approved for the treatment of refractory depression Rush et al, 2005), these procedures also reduce pain in patients suffering from chronic pain induced by migraines and cluster headaches (Hord et al, 2003;Multon and Schoenen, 2005) and from chronic pelvic pain (Napadow et al, 2012). Several case reports demonstrate electroconvulsive therapy effectiveness in the treatment of comorbid chronic pain and depression (Suzuki et al, 2009;Wasan et al, 2004).…”
Section: Non-pharmacologic Alternative Therapiesmentioning
confidence: 97%
“…These studies also reported that the improvement in angina symptoms persisted after the cessation of tVNS treatment for up to 3 weeks. Recently, tVNS using surface electrodes has been investigated as a possible analgesic (15,36) and has also been trialled as an alternative to invasive cervical VNS in patients with refractory epilepsy (14). These studies also monitored heart rate and blood pressure and reported no significant changes.…”
Section: Tvns Effects On Cardiovascular Autonomic Functionmentioning
confidence: 99%
“…This stimulation can be performed transcutaneously by applying surface electrodes or acupuncture needles to the external ear (tVNS). Such tVNS has been trialled in patients with coronary artery disease (12,13), epilepsy (14) and chronic pain (15), however, the outcomes investigated are varied and mostly subjective. In addition, the stimulation parameters used differ widely, therefore, little is known about the optimal parameters for tVNS.…”
Section: Introductionmentioning
confidence: 99%